The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1186/1471-2296-15-121
|View full text |Cite
|
Sign up to set email alerts
|

Prostate specific antigen testing is associated with men’s psychological and physical health and their healthcare utilisation in a nationally representative sample: a cross-sectional study

Abstract: BackgroundProstate cancer incidence has risen considerably in recent years, primarily due to Prostate Specific Antigen (PSA) testing in primary care. The objective of this study was to investigate associations between PSA testing and the psychological and physical health, and healthcare utilisation of men in a population where PSA testing is widespread.MethodsA cross-sectional study was carried out in a population-representative sample of men ≥50 years enrolled in The Irish Longitudinal Study on Ageing (TILDA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…However, we expect that women are unlikely to continue filling prescriptions for medication they no longer take. It is important to consider that statins may be preferentially prescribed for, and taken by, patients who engage in healthier behaviours and have superior health outcomes ( Evans et al , 1995 ; Brookhart et al , 2007 ; Flahavan et al , 2014 ). This is known as healthy-user bias and may cause an overestimation of any beneficial effect of statins ( Glynn et al , 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, we expect that women are unlikely to continue filling prescriptions for medication they no longer take. It is important to consider that statins may be preferentially prescribed for, and taken by, patients who engage in healthier behaviours and have superior health outcomes ( Evans et al , 1995 ; Brookhart et al , 2007 ; Flahavan et al , 2014 ). This is known as healthy-user bias and may cause an overestimation of any beneficial effect of statins ( Glynn et al , 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…This they hypothesise may be due to (i) adherent patients being ‘more health seeking’ and therefore more likely to seek or agree to take other preventative interventions and tests and/or (ii) differences in health status (physical and cognitive) between the two groups, with those who are adherent being healthier. Additionally, men with poorer psychological health have been found to be less likely to have PSA tests [ 32 34 ]. Moreover, those predisposed to poorer psychological health are also predisposed to poor wellbeing throughout their disease trajectory [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also evaluated potential variables associated with a PSA request that was potentially non-compliant with the current guideline. We speculated that some specific patient characteristics (diabetes diagnosis [ 8 , 9 ], consuming tobacco, alcohol, or other drugs [ 10 , 11 ]) could be associated with lower probability of having a potentially non-compliant PSA test due to lower testing frequency. Nevertheless, although we found no difference in PSA test compliance with the guideline in patients with diabetes diagnoses, those who were current consumers of tobacco, alcohol, and/or other drugs showed 20% lower potential non-compliance.…”
Section: Discussionmentioning
confidence: 99%
“…PSA non-compliance in these patients was partially explained by shorter life expectancy, but patients diagnosed with another neoplasm had an 18% higher frequency of potentially non-compliant PSA petitions after adjusting for age and life expectancy. Available evidence has reported that patients with a previous cancer diagnosis were more likely to have a PSA test [ 10 ], which could be due to increased contact with healthcare services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation